Genetic variants associated with physical and mental characteristics of the elite athletes in the Polish population - Peplonska, B.; Adamczyk, J. G.; Siewierski, M.; Safranow, K.; Maruszak, A.; Sozanski, H.; Gajewski, A. K.; Zekanowski, C. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The aim of the study was to assess whether selected genetic variants are associated with elite athlete performance in a group of 413 elite athletes and 451 sedentary controls. Polymorphisms in ACE, ACTN3, AGT, NRF-2, PGC1A, PPARG, and TFAM implicated in physical performance traits were analyzed. Additionally, polymorphisms in CHRNB3 and FAAH coding for proteins modulating activity of brain's emotion centers were included. The results of univariate analyses indicated that the elite athletic performance is associated with four polymorphisms: ACE (rs4341, P = 0.0095), NRF-2 (rs12594956, P = 0.011), TFAM (rs2306604, P = 0.049), and FAAH (rs324420, P = 0.0041). The multivariate analysis adjusted for age and gender confirmed this association. The higher number of ACE D alleles (P = 0.0021) and the presence of NRF-2 rs12594956 A allele (P = 0.0067) are positive predictors, whereas TFAM rs2306604 GG genotype (P = 0.031) and FAAH rs324420 AA genotype (P = 0.0084) negatively affect the elite athletic performance. The CHRNB3 variant (rs4950, G allele) is significantly more frequent in the endurance athletes compared with the power ones (P = 0.025). Multivariate analysis demonstrated that the presence of rs4950 G allele contributes to endurance performance (P = 0.0047). Our results suggest that genetic inheritance of psychological traits should be taken into consideration while trying to decipher a genetic profile of top athletic performance.